2020
DOI: 10.1017/s0144686x20001488
|View full text |Cite
|
Sign up to set email alerts
|

Engagement with life among the oldest-old in assisted living facilities: enriching activities and developmental adaptation to physical loss

Abstract: The objective of this study was to examine the activities, motivations, and barriers of activity engagement in the oldest-old residing in assisted living facilities (ALFs). Semi-structured interviews were conducted with 20 participants, aged 80–94 (standard deviation = 4.38), from two ALFs. Thematic analyses were used to identify and corroborate clusters of experiences. All residents stated that they desired enriching activities, most often in the form of productive work or community events. Although engaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…This pilot study is consistent with previous research that ICT can work for a variety of clients ( Ho, 2018 ; Jones, 2019 ; Kim, 2021 ; Masina et al, 2020 ; O’Brien et al, 2020 ; Pradhan et al, 2018 ), while also benefitting caseworkers, facilities, and clients’ families. Although, we were unable to measure these constructs directly, these results align with previous research on technology’s ability to reduce isolation or loneliness and provide stimulation, engagement, and entertainment for older adults and those with IDDs ( Boeder et al, 2020 ; Demiris et al, 2008 ). Although we were unable to interview facility staff, such devices have the potential to enhance resident cognitive engagement.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This pilot study is consistent with previous research that ICT can work for a variety of clients ( Ho, 2018 ; Jones, 2019 ; Kim, 2021 ; Masina et al, 2020 ; O’Brien et al, 2020 ; Pradhan et al, 2018 ), while also benefitting caseworkers, facilities, and clients’ families. Although, we were unable to measure these constructs directly, these results align with previous research on technology’s ability to reduce isolation or loneliness and provide stimulation, engagement, and entertainment for older adults and those with IDDs ( Boeder et al, 2020 ; Demiris et al, 2008 ). Although we were unable to interview facility staff, such devices have the potential to enhance resident cognitive engagement.…”
Section: Discussionsupporting
confidence: 71%
“…Prior to COVID-19, ICT use was primarily initiated by LTC facility residents to communicate with friends, family, and supports. Residents have also used ICTs for entertainment (e.g., watching movies), stimulation (e.g., puzzles), and information (e.g., news; Baker et al, 2018 ; Blaschke et al, 2009 ; Boeder et al, 2020 ; Chen & Schulz, 2016 ; Demiris et al, 2008 ). Several studies found that ICTs reduce social isolation and loneliness and increase stimulation and social connectedness in LTC facilities ( Baker et al, 2018 ; Chen & Schulz, 2016 ; Edelman et al, 2020 ; Ibarra et al, 2020 ; Kluck et al, 2021 ).…”
Section: Background and Objectivesmentioning
confidence: 99%